Pengaruh Kedisiplinan Terhadap Kinerja Pegawai Pada Kantor Badan Pengelola Hutan Produksi (BPHP) Wilayah XIII Makassar - Andi Irfan (Jurnal Online Manajemen ELPEI, 2022)
This research was conducted at the Office of the Production Forest Management Agency (BPHP) Wil XIII Makassar in early August to mid-October 2021. Sampling in this study was used as many as 63 respondents, the method used in this study is the quantitative method with the data collection technique is through a questionnaire distributed to respondents. The analysis used in this research is descriptive analysis using simple linear regression with hypothesis testing using t test with a significant level of 5%, this research uses SPSS Version 25. From a simple linear regression analysis, it shows that employee performance is influenced by the discipline variable. The result of determination (R2) uses the value of Adjested r square, because it uses regression with one dependent variable, namely 0.785, which means that the Discipline Variable is able to affect employee performance by 78.5% while the remaining 21.5% is influenced by other variables not examined. From the calculation of the t test, it can be seen that the Discipline Variable partially has an effect on Employee Performance.